The effect of adjuvant chemotherapy on symptom burden and quality of life over time; a preliminary prospective observational study using individual data of patients aged ≥ 70 with early stage invasive breast cancer. Issue 2 (March 2018) - Quinten, Chantal; Kenis, C.; Hamaker, M.; Coolbrandt, A.; Brouwers, B.; Dal Lago, L.; Neven, P.; Vuylsteke, P.; Debrock, G.; Van Den Bulck, H.; Smeets, A.; Schöffski, P.; et al.
Abstract: Objectives: We aim to assess short and long term effects of chemotherapy on patient-reported quality of life (QOL) and patient versus clinician symptom reporting in older patients with breast cancer adjusted for tumour and aging parameters. Material and Methods: In this prospective, multicentre, non-interventional, observational study, women aged ≥ 70 years were enrolled after surgery and assigned to a TC chemotherapy (docetaxel and cyclophosphamide) group or a control group depending on their planned adjuvant treatment. Longitudinal multivariate models were used to assess the statistical and minimal clinically important difference (MCID) in the impact of TC chemotherapy over time on QOL and symptom burden adjusted for baseline aging and tumour parameters. Statistical significance was set at 5% and MCID at 10 points. Results: In total, 57 patients were enrolled in the chemotherapy and 52 patients in the control group. Within the chemotherapy group, clinical deterioration was reported at 3 months for Fatigue (17.73), Dyspnoea (17.05), Diarrhoea (12.06) and Appetite Loss (17.05) scores (all p < 0.001). However, the scores had returned to baseline (or even better for Role Functioning) at year 1. No clinical deterioration was reported in the control group. Symptom scores as reported by patients were significantly (p < 0.05) higher than those reported by the clinicians, even more so for Fatigue, Dyspnoea, and Pain. Conclusion: Our results show that symptom burden and diminished QOL in an older breast cancer population receiving adjuvant TC chemotherapy are short-lived and disappear after a while with no long-term differences compared to a similar population not receiving chemotherapy.